Whiteness, Power, and Resisting Change in US Higher Education A Peculiar Institution - Roth, Kenneth R.; Ritter, Zachary S.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2021)
This edited volume connects the origins of US higher education during the Colonial Era with current systemic characteristics that maintain white supremacist structures and devalue students and faculty of color, as well as areas of study that interrogate Whiteness. The authors examine power structures within the academy that scaffold Whiteness and promote inequality at all levels by maintaining a two-tier faculty system and a dearth of Faculty and Administrators of Color. Finally, contributors offer systemic and collective solutions toward a more equitable redistribution of power, primarily among faculty and administration, through which other inequities may be identified and more easily addressed.
1. Historical Scaffolds of Whiteness in Higher Education -- 2. Confronting Ourselves: An Autoethnographic Approach to Whiteness in Higher Education -- 3. Counter-Narratives as Critical Invitations for Change: Race-Centered Policy Making and Backlash at Peculiar Institutions -- 4. International Students Need Not Apply: Impact of US Immigration Policy in the Trump Era on International Student Enrollment and Campus Experiences -- 5. Neoliberalism, Neopopulism, and Democracy in Decline: The University Under Attack on Multiple Fronts -- 6. A Matter of Academic Freedom -- 7. Changing Pathways of Historically Black Colleges and Universities: Any Place for Afrocentric Ideas? -- 8. The Changing Exasperations of Higher Education -- 9. Resisting the Neoliberal university via a General Strike -- 10. Abolish the Lecturer: A Manifesto for Faculty Equity -- 11. Racist Algebra of Abjection: A Template of Racial Violence.
Keywords: Educational sociology; Education, Higher; Education and state; Sex; Critical criminology; Sociology of Education; Higher Education; Education Policy; Gender Studies; Critical Criminology